(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
Half Diallel cross was conducted in Bouka research station among four cultivars of Triticum durum which were grown in (2014 2015) and crossing in (2015 2016) seasons. The study was made on the following characteristice : days of heading , grain filling period plant heading and the spike length to assess the general and special combining ability and heterosis . The result showed that the variation of varieties and hyprids was significant and highly significant for the whole studiet characteristics . This indicates to the genetic diverge between the cultivars , also the result showed a superiority of ’’sham7’’ on the rest of the studied varieties in spike length and days of heading because it had significant and highly significant effects for these characteristics, it also showed a superiority of ’’Duma1’’ on the rest of cultivars in plants hright characteristic because it owened negative significant effect in general combining ability, and the possibility of making use of these varieties to improve the characteristics mentioned above. The hybrid (Sham7.Bohoth11) showed the best specific Combining ability for Characters spike length and the plant height , while the hybrid (Sham7.Acsad65) showed the best specific combining ability for Days of heading character . But The hybrid (Bohoth11.Doma1) showed the best specific Combining ability for the grain filling period character. The ratio of general ability to specific ability showed domination of the non additive gene action to inheritance all the studied Characters. أجري تهجين نصف تبادلي في محطة أبحاث بوقا التابعة لجامعة تشرين بين أربعة أصناف من القمح القاسي وهي : شام7 , اكساد65 , بحوث11 , دوما1 , حيث تمت الزراعة في الموسم الزراعي2014-2015 وأجريت عملية التهجين في الموسم الزراعي 2015-2016. تم دراسة الصفات التالية: فترة النمو الخضري, فترة امتلاء الحبوب, ارتفاع النبات وطول السنبلة , وذلك لتقدير القدرة العامة والقدرة الخاصة على التوافق وقوة الهجين . بينت النتائج وجود تباين معنوي وعالي المعنوية للأصناف الأبوية والهجن الناتجة عنها لجميع الصفات المدروسة , وهذا يشير إلى التباعد الوراثي بين الآباء المستخدمة في التهجين . أظهرت النتائج تفوق الصنف شام7 على بقية الأصناف المدروسة لصفة طول السنبلة وفترة النمو الخضري حيث امتلك تأثيرات معنوية وعالية المعنوية بالنسبة لهذه الصفات , وتفوق الصنف دوما1 على بقية الأصناف لصفة ارتفاع النبات حيث امتلك تأثيرات سلبية معنوية للقدرة العامة على التوافق , وبتالي امكانية استخدام هذه الأصناف لتحسين الصفات المذكورة سابقاً. أظهر الهجين (شام7*بحوث11) أفضل قدرة خاصة على التوافق لصفات طول السنبلة وارتفاع النبات , فيما كان للهجين (شام7*أكساد65) أفضل قدرة خاصة على التوافق لصفة فترة النمو الخضري وللهجين (بحوث11*دوما1) أفضل قدرة خاصة لصفة فترة امتلاء الحبوب. أظهرت نسبة تباين القدرة العامة إلى الخاصة سيطرة الفعل المورثي اللاإضافي على وراثة كل الصفات المدروسة .